IMPLEMENTASI PENGELOLAAN ASSET DAERAH ( STUDI KASUS ALIH FUNGSI LAHAN TERMINAL MENJADI PUSAT PEMERINTAHAN DI KOTA PADANG ) - Putra, Dery Eka; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this study is to determine how the asset management area in Padang city afterland use terminal into the center of goverment. Where by looking at the management of manylands that were previously found new purpose terminals such as terminal of Andalas andgoan hoat.The result of study found several factors that effect the asset management area interminal divert land functioned as asset management area is human resources, financialresources and area infrastructure. The most dominal factor in asset management in Padangis financial resources.This research was conducted in Padang. Exactly, financial services and assetmanagement, and DPRD Padang where becoming population and sample in this study wasofficers or employees of a financial services and asset managemnt and employees ofparliament/DPRD Padang, samples using in this study was a sampling technique, datacollection is the method of observation, interview and documentation after the data colletedanalyzed using qualitative and descriptive analysis.After this research study was found that asset management area in Padang was notgood, this thing can be seen the from G.R Terry theory are reviewed based on four indicatorsie: planning, organizing, actuating dan controling.Keywords : asset area of Padang,management, planning, organizing, actuating dancontroling.